2023
DOI: 10.3390/jcm12123966
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Clinical Features of Post-COVID-19 Patients—Symptoms, Fatigue and Physical Function at 3- and 6-Month Follow-Up

Abstract: Post-COVID-19 syndrome (PCS) has been described as ‘the pandemic after the pandemic’ with more than 65 million people worldwide being affected. The enormous range of symptoms makes both diagnosis complex and treatment difficult. In a post-COVID rehabilitation outpatient clinic, 184 patients, mostly non-hospitalized, received a comprehensive, interdisciplinary diagnostic assessment with fixed follow-up appointments. At baseline, three in four patients reported more than 10 symptoms, the most frequent symptoms w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 48 publications
2
7
1
Order By: Relevance
“…This upward trend was statistically significant in the case of fatigue experienced after work (for all, and women) and after a long train journey (for women). Our results diverged from those studies that reported decreasing levels of fatigue over time in COVID-19 patients (Fumagalli et al, 2022; Steinmetz et al, 2023; Van Herck et al, 2021). However, they align with the findings of a study that observed a trend of increasing fatigue over the months 1, 3, 6, and 12 following the onset of COVID-19 infection (Mazza et al, 2022).…”
Section: Discussioncontrasting
confidence: 99%
“…This upward trend was statistically significant in the case of fatigue experienced after work (for all, and women) and after a long train journey (for women). Our results diverged from those studies that reported decreasing levels of fatigue over time in COVID-19 patients (Fumagalli et al, 2022; Steinmetz et al, 2023; Van Herck et al, 2021). However, they align with the findings of a study that observed a trend of increasing fatigue over the months 1, 3, 6, and 12 following the onset of COVID-19 infection (Mazza et al, 2022).…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings are consistent with a large Canadian study that identified fatigue as a significant predictor of declining health-related quality of life after COVID-19 [40]. Although physical function and quality of life improve over time in COVID-19 survivors, an impairment in these health-related outcomes persists in a significant proportion of patients [40,41]. These data suggest that HGS should be assessed soon after discharge to identify patients who may need additional care to improve their health status.…”
Section: Discussionsupporting
confidence: 89%
“…Their cognitive function showed statistically significantly improvement and their health-related quality of life had increased by 0.11 points, a value clearly above the threshold of 0.03 previously described to be clinically relevant [23]. The fact that secondary outcomes such as memory and concentration capacity also improved in the control group could be explained by a natural amelioration of PCS symptoms over time, which has also been observed by other researchers [24]. Importantly, only patients receiving interactive OT showed significant improvement of all measured endpoints of cognitive function, occupational problems, quality of life, and social participation.…”
Section: Discussionsupporting
confidence: 79%